Ground-based stratospheric O 3 and HNO 3 measurements at Thule, Greenland: an intercomparison with Aura MLS observations - I. Fiorucci; G. Muscari; L. Froidevaux; M. L. Santee (Atmospheric Measurement Techniques, 2013)
In response to the need for improving our understanding of the evolution and the interannual variability of the winter Arctic stratosphere, in January 2009 a Ground-Based Millimeter-wave Spectrometer (GBMS) was installed at the Network for the Detection of Atmospheric Composition Change (NDACC) site in Thule (76.5° N, 68.8° W), Greenland. In this work, stratospheric GBMS O 3 and HNO 3 vertical profiles obtained from Thule during the winters 2010 (HNO 3 only), 2011 and 2012 are characterized and intercompared with co-located measurements of the Aura Microwave Limb Sounder (MLS) experiment. Using a recently developed algorithm based on Optimal Estimation, we find that the GBMS O 3 retrievals show good sensitivity (> 80%) to atmospheric variations between ~ 17 and ~ 50 km, where their 1σ uncertainty is estimated to be the larger of ~ 11% or 0.2 ppmv. Similarly, HNO 3 profiles can be considered for scientific use between ~ 17 and ~ 45 km altitude, with a 1σ uncertainty that amounts to the larger of 15% or 0.2 ppbv. Comparisons with Aura MLS version 3.3 observations show that, on average, GBMS O 3 mixing ratios are biased negatively with respect to MLS throughout the stratosphere, with differences ranging between ~ 0.3 ppmv (8%) and 0.9 ppmv (18%) in the 17–50 km vertical range. GBMS HNO 3 values display instead a positive bias with respect to MLS up to 26 km, reaching a maximum of ~ 1 ppbv (10%) near the mixing ratio profile peak. O 3 and HNO 3 values from the two datasets prove to be well correlated at all altitudes, although their correlations worsen at the lower end of the altitude ranges considered. Column contents of GBMS and MLS O 3 (from 20 km upwards) and HNO 3 (from 17 km upwards) correlate very well and indicate that GBMS measurements can provide valuable estimates of column interannual and seasonal variations for these compounds.